Are Formal Planners More Likely To Achieve New Venture Viability? A Counterfactual Model And Analysis. (8th February 2017) - Greene, Francis J.; Hopp, Christian
Abstract : Research Summary: This study develops and tests a counterfactual model of the relationship between formal written business plans and the achievement of new venture viability. This is important because extant theory remains oppositional, and there is a practical need to provide guidance to founders on the utility of formal plans. To test our model, we use propensity score matching to identify the impact that founder, venture, and environmental factors have on the decision to write a formal plan (selection effects). Having isolated these selection effects, we test whether or not these plans help founders achieve venture viability (performance effects). Our results, using data on 1, 088 founders, identify two key results: (1) selection effects matter in the decision to plan; and (2) it pays to plan. Managerial Summary: This study assesses whether founders who write formal plans are more likely to achieve new venture viability. This is important because, despite its popularity, there is considerable debate about the value of plans. One root reason for this is that what prompts a founder to plan also impacts his/her chances of creating a viable new venture. The study's novelty is to separate out influences on the decision to plan from the plan‐venture viability relationship. Our results show that better‐educated founders, those wanting to grow and innovate, and those needing external finance are more likely to plan. Subsequently, having isolated what prompts planning, we assess if writing a plan actually promotes venture viability. We find that it pays to plan. Copyright © 2016 Strategic Management Society.